Pelatihan Identifikasi dan Konservasi Mangrove Bagi Kelompok Pemandu Ekowisata di Desa Palaes Minahasa Utara, Sulawesi Utara: (Training on Mangrove Identification and Conservation for Ecotourism Guide Group in Palaes Village, North Minahasa, North Sulawesi) - Tilaar, Ribka Mega; Mawuntu, Estalina; Tanjung, Gadis Sabrina; Setiawan, Denny Christian; Gobel, Iga Mawarni; Taarape, Taarape; Ballamu, Larry Lowrend; Pontoh, Citra Julia; Nengsih, Reskiyah; Aisyah, Nur’; Fabiolani, Fidelia Anninda; Koneri, Roni (Sam Ratulangi University, 2024)
A mangrove ecosystem is an area that develops in tidal areas with muddy substrates. The existence of mangrove ecosystems in an area functions ecologically, economically, and socially. The beauty of the mangrove landscape provides an attraction that can be used as an ecotourism destination. The problem at this time is still lacking understanding and skills of guides and mangrove ecotourism governance in Palaes Village regarding mangrove identification and conservation. This activity aims to increase the knowledge, understanding, and skills of ecotourism guides and governance groups in identifying and conserving mangrove forests in Palaes Village, North Minahasa, and North Sulawesi. The implementation method uses a participatory approach through lectures, discussions, and training with observation and identification of mangroves in mangrove ecotourism areas, mentoring, and monitoring. The results of the activity indicated an increase in knowledge and understanding and skills of participants in mangrove identification and conservation. The use of various methods such as discussions, and going directly to the mangrove ecosystem aroused the enthusiasm of participants to participating in the activity. This activity also provides positive results for guides and mangrove governance in mangrove identification and conservation. The results of the identification training resulted in the identification of 7 mangrove species in the mangrove ecotourism area of Palaes Village. Keywords: Training; conservation; ecology; identification; Palaes ABSTRAK Ekosistem mangrove merupakan suatu kawasan yang berkembang pada daerah pasang surut dengan substrat berlumpur. Keberadaan ekosistem mangrove pada suatu kawasan berfungsi secara ekologi, ekonomi dan sosial. Keindahan lanskap mangrove memberikan daya tarik untuk dijadikan destinasi ekowisata. Permasalahan pada saat ini masih kurang pemahaman dan keterampilan pemandu dan tata kelola ekowisata mangrove di Desa Palaes tentang identifikasi dan konservasi mangrove. Kegiatan ini bertujuan untuk meningkatkan pengetahuan, pemahaman, dan keterampilan kelompok pemandu dan tata kelola ekowisata dalam identifikasi dan konservasi hutan mangrove di Desa Palaes Minahasa Utara, Sulawesi Utara. Metode pelaksanaan menggunakan pendekatan partisipatif yaitu melalui ceramah, diskusi, dan pelatihan dengan pengamatan dan identifikasi mangrove di kawasan ekowisata mangrove, pendampingan dan monitoring. Hasil kegiatan didapatkan terjadi peningkatan pengetahuan dan pemahaman serta keterampilan peserta dalam identifikasi dan konservasi mangrove. Penggunaan berbagai metode seperti diskusi, dan turun langsung ke ekosistem mangrove membangkitkan semangat peserta dalam mengikuti kegiatan. Kegiatan ini juga memberikan hasil yang positif bagi pemandu dan tata kelola mangrove dalam identifikasi mangrove dan konservasinya. Hasil pelatihan identifikasi didapatkan 7 spesies mangrove pada kawasan ekowisata mangrove Desa Palaes.